Digitalisasi Administrasi Pemerintahan Desa: Upaya Meningkatkan Pelayanan Publik di Desa Sungai Pinang - Alkadafi, Muammar; Rachmad, Ferizal; April, Muhammad (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: The high expectations of the community in Sungai Pinang Village for digital-based administrative services highlight the need for a transformation in the working system of village officials towards more modern and efficient service delivery. This community engagement programme aims to shift the village administrative service system from manual to digital through the implementation of a village public service application. Method: The programme applied the Participatory Rural Appraisal (PRA) method with a participatory planning approach involving local stakeholders. The stages consisted of observation, interviews, and pre-tests to identify the needs and readiness of village officials, followed by training on both manual and digital administrative systems in collaboration with PT Digital Desa Indonesia. Results: The activities demonstrated a significant improvement in the knowledge and skills of village officials, alongside a shift in working practices towards digitalisation. The implementation of the digital village application had a positive impact on the efficiency, effectiveness, and quality of administrative services, while also enhancing transparency and public satisfaction. Conclusion: This programme successfully encouraged the transformation of village administrative services through participatory approaches, training, and technical assistance. It strengthened the capacity of village officials and fostered governance that is modern, adaptive, participatory, and data-driven.